Performance of mid-size combine harvester of grain corn on the field efficiency and energy consumption at the northern Johor of Malaysia - Masroon, Mohamad Hairie; Mat Nawi, Nazmi; Yahya, Azmi; Mohamad Shukery, Mohamad Firdza (Universiti Putra Malaysia Press, 2020)
A mid-size combine harvester with 2.76 m reaping width and 103.53 hp engine output has been employed in grain corn production, especially by small-scale grain corn farmers. This study attempted to determine field performances of a typical mid-size combine harvester by measuring its effective field capacity (EFC), field efficiency (FE), fuel consumption (FC) and field machine index (FMI). Different types of energy inputs such as fuel, machinery, human, included direct, indirect, renewable and non-renewable energy involved in grain corn harvesting were also measured. The field measurements were carried out in 3 ha of grain corn farm, under similar field conditions using a typical mid-size combine harvester. The average values of EFC, FE, FC and FMI for the mid-size combine harvester were found to be 0.23 ha/h, 34.97%, 37.25 lit/ha and 0.91, respectively. The average equivalent energy values of fuel, machinery and human energy were 1780.70 MJ/ha, 587.73 MJ/ha and 8.53 MJ/ha, respectively. The average values of the direct and indirect energy were 1789.23 MJ/ha and 587.73 MJ/ha, respectively. The average values of renewable and non-renewable energy were recorded at 8.53 MJ/ha and 2368.42 MJ/ha, respectively. The mid-size combine harvester investigated in this study exhibited good field performance characteristic using a reasonable amount of energy consumption as compared to harvesting operation for other grain crops. From the results, it can be concluded that good practice in harvesting operation could improve field performance, and minimise operational costs and energy consumption.